Tomatillo (Physalis ixocarpa) as a Natural New Host for Tomato yellow leaf curl virus in Sinaloa, Mexico - Gámez-Jiménez, C (Plant disease, 2009)
Tomatillo, also known as husk or green tomato, is cultivated in 29 of 32 states in Mexico, with the main production areas located in the states of Sinaloa, Michoacán, Puebla, Sonora, Guanajuato, Jalisco, and Hidalgo. The national production of tomatillo in 2006 was 805,721 tons with a value of $259 million. Tomato yellow leaf curl virus (TYLCV) is one of the most damaging begomoviruses affecting tomato worldwide. TYLCV was first identified in Mexico in 1999 in Yucatán (1) and most recently identified as infecting tomato in Sinaloa (3). During December of 2006, symptoms including chlorotic margins, yellowing, and interveinal yellowing were observed in tomatillo fields. Symptomatic plants were associated with the presence of whiteflies in many fields, suggesting a begomovirus etiology. Total DNA was extracted from leaves of 77 symptomatic tomatillo plants from Guasave and Ahome counties and amplified by PCR using a degenerate primer pair (2). These primers can differentiate between monopartite and bipartite begomoviruses on the basis of the size of the amplification products, approximately 750 and 650 bp, respectively. A PCR product of 742 bp was obtained from 48 of 97 samples. The PCR product of two representative samples from each county were cloned into pGEM-T Easy Vector (Promega, Madison, WI) and sequenced. The sequences of the four amplicons were identical (GenBank Accession No. EU224314) and were compared with sequences of others begomoviruses in the NCBI/GenBank database using the Clustal V alignment method (MegAlign, DNASTAR software, London). The highest sequence identity of 100% was with a TYLCV isolate from Sinaloa (GenBank Accession No. DQ377367), 99.8% with a TYLCV isolate from Tosa (GenBank Accession No. AB192965), 98.4% with a TYLCV isolate from China (GenBank Accession No. AM282874), 95.8% with a TYLCV isolate from Yucatán (GenBank Accession No. AF168709), and 94.6% with TYLCV-Is (GenBank Accession No. X15656). The genome of tomatillo TYLCV isolate was amplified using PCR and overlapping primer pair (TYLCV NcoI Forward GGCCCATGGCCGCGCAGCGG and Reverse CGGCCATGGAGACCCATAAG). Sequence of a 2,781-bp fragment was obtained (GenBank Accession No. FJ609655) and sequence analysis corroborated that the tomatillo TYLCV has 99.3% identity with two TYLCV isolates from Sinaloa (GenBank Accession Nos. EF5234478 and FJ012358). To our knowledge, this is the first report of tomatillo as a natural host of TYLCV in Mexico. These results suggest that TYLCV has begun to establish itself in others crops since it was first reported to be infecting tomato in Sinaloa, Mexico. References: (1) J. T. Ascencio-Ibañez et al. Plant Dis. 83:1178, 1999. (2) J. T. Ascencio-Ibañez et al. Plant Dis. 86:692, 2002. (3) C. Gámez-Jímenez et al. (Abstr.) Phytopathology 96(suppl.):S38. 2006